Does intraoperative cell salvage remove cobalt and chromium from reinfused blood? - Reijngoud, L; Pattyn, C; De Haan, R; De Somer, F; Campbell, P; Gill, H; De Smet, K (2009)
In 12 patients undergoing a revision hip arthroplasty after a failed metal-on-metal primary hip arthroplasty, the effectiveness of intraoperative cell salvage (ICS) in removing metal ions was investigated. Samples of blood collected during surgery were filtered using 2 ICS devices. The samples had the concentrations of cobalt (Co) and chromium (Cr) measured before and after filtration. There was an average reduction of 76.3% for Cr concentration and 78.6% for Co concentration after ICS filtering. The Co-to-Cr ratio before and after filtration was similar. At the present time, these salvage systems should be used with caution in the patient undergoing revision of metal-on-metal bearing surfaces.